Development and Preliminary Psychometric Evaluation of a Patient-Reported Outcome Measure for Lung Cancer Stigma: The Lung Cancer Stigma Inventory (LCSI) - Hamann, Heidi A. (Stigma Health, 2017)
INTRODUCTION: Among patients with lung cancer, stigma is associated with negative psychosocial and behavioral outcomes. There is a need to develop psychometrically robust patient-reported outcome (PRO) measures for stigma that incorporate perspectives of patients diagnosed with lung cancer. As part of our multi-phase process of measure development and validation, we report on scale formation and preliminary psychometric evaluation of the Lung Cancer Stigma Inventory (LCSI). METHOD: Building on previously reported concept elicitation (Phase I) work, Phase II of LCSI development involved item generation and refinement, informed by literature review, provider input, and patient (N=20) feedback. Phase III focused on initial psychometric scale evaluation in a unique sample of 231 lung cancer patients. RESULTS: Based on provider input and patient cognitive interviews, 49 items were included in a preliminary measure. In an exploratory factor analysis (EFA) of the 37 retained items, three factors emerged: Perceived Stigma, Internalized Stigma, and Constrained Disclosure. Internal consistency of the final, 25-item LCSI scale was high (Cronbach’s alpha= 0.89) and the three subscales demonstrated good internal consistency. The test-retest correlation was high (r = 0.91), suggesting strong stability of measurement over time. There was good convergent validity between the LCSI and an existing measure of lung cancer stigma, the Cataldo Lung Cancer Stigma Scale (CLCSS; r= 0.58, p< 0.001). DISCUSSION: In a multi-phase process, we have developed a reliable, multi-dimensional measure of lung cancer stigma, the Lung Cancer Stigma Inventory (LCSI). Subsequent work will be conducted to establish further evidence of validity and clinically meaningful change.